Positions and Interests in the 1856 Treaty of Paris Negotiations - Gheorghe, Stefan; Pișleag, Țuțu (Acta Universitatis Danubius. Relationes Internationales, 2024)
For almost a century, until the middle of the 19th century, the Romanian Principalities are periodically subjected to "several categories of social misfortunes: wars; military invasions; robbery operations; scales; extreme natural events (drought, floods, earthquakes, locust invasions), epidemics as well as fires, quite numerous in the urban environment". Both in Wallachia and in Moldova, an "antagonism between the great and the small nobility, of identical origin, but with unequal privileges, existed since the 17th century...".